Pengaruh Social Media Marketing dan E-Trust Terhadap Minat Beli pada Mahasiswa Pendidikan Ekonomi FKIP Universitas Jambi - Afiqoh, Ika Kumala; Arpizal, Arpizal; Sahara, Sahara (Dinasti Review Publisher, 2024)
The aim of this research is to find out how media marketing and trust variables influence buying interest in economics education students at FKIP Jambi University Class of 2020 – 2021 (study on open stall e-commerce). This research uses quantitative research. The population of this study consisted of 121 students of the Economic Education Study Program class of 2020. The data collection method used Google forms to distribute questionnaires. The data analysis techniques used are descriptive analysis, normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple regression analysis test, t test, f test, and coefficient of determination test. The research results show that partially the social media marketing variable has a positive and significant effect on interest with a tcount value of 3,583> ttable of 1,979 with a sig value of 0.000 < 0.05. Partially, the variable cannot have a positive and significant influence between the E-Trust variable on buying interest with a t value of 0.315 < t table of 1.979 with a sig value of 0.753 > 0.05. Simultaneously, there is a positive and significant influence between social media marketing and e-trust variables on purchasing interest as evidenced by the fcount value of 6.45 from the ftable of 3.92. So H_(a) is accepted and H_0 is rejected, so there is a significant influence between self-efficacy and entrepreneurial skills on entrepreneurial interest.